On the Basis of Sex - Leder, Mimi, 1952-; Jones, Felicity; Hammer, Armie, 1986-; Theroux, Justin (Universal City, CA : Universal Pictures Home Entertainment, 2019)
The story of Ruth Bader Ginsburg, a woman who overcame gender inequalities in order to become a Supreme Court Justice.
Wide screen 1.85:1.
Felicity Jones, Armie Hammer, Justin Theroux, Sam Waterston, Kathy Bates.
MPAA rating: PG-13.
Keywords: Ginsburg, Ruth Bader, -- 1933-2020 -- Drama; Women judges -- United States -- Drama; Legal films; Fiction films; Feature films; Biographical films